EVALUATION OF THE SECURITY OF THE USE OF GUAJAVA PSIDIUM EXTRACT CAPSULE ON HEART FUNCTION IN DENGUE FEVER AND DENGUE HEMORAGIC FEVER PATIENTS IN TYPE C HOSPITAL - Agamasi, Amalia; Darmawan, Endang; Akrom (Transpublika Publisher, 2022)
There are 126,675 DHF sufferers in 34 provinces and 1,229 of them died, while the Incidence Rate (IR) in Central Java is 47.9 per 100,000 population. Based on the safety of Psidium guajava Linn on the liver by calculating the lethal dose average showed that there were no deaths from the two experimental models of Swiss mice and Wistar mice in the dose range up to 2,000 mg/kg BB. Safety tests in rats proved lethal dose 50 (LD50) of guava leaf extract more than 5 g/kg. This study aims to determine the effect of psidii capsules containing guava leaf extract (Psidium guajava Linn.) toward levels (SGOT and SGPT) of DF and DHF patients in PKU Muhammadiyah Wonosobo Hospital. This study belongs to perspective cohort analytic observational using blood plasma patients of PKU Muhammadiyah Wonosobo Hospital of 37 patients in the period of March to August 2018 which were divided into two groups, namely standard therapy + guava leaf extract capsules and the group receiving standard therapy only. Dosage of Psidium guajava 3x2 capsules for 3 to 4 days. Examination of SGOT and SGPT levels used UV-vis spectrophotometry. General linear model was used for analyzing the data. The average SGOT level after treatment was 64 U/L in DF and 99 at DHF while the SGPT levels were 30 U/L and 35 U/L. Average levels of SGOT and SGPT decreased. There were no differences in SGOT and SGPT mean of DF and DHF patients in the two groups after giving guava leaf extract capsules with p>0.05. In SGOT mean, there was an increase in SGOT after giving guava leaf extract probably because there were patients who had chronic liver disorders. Keywords: Dengue Fever, Dengue Hemorrhagic Fever, Guava extract capsule, SGOT SGPT